Methane Seeps on the US Atlantic Margin and Their Potential Importance to Populations of the Commercially Valuable Deep-Sea Red Crab, Chaceon quinquedens - Turner, Phillip J.; Ball, Bernard; Diana, Zoie; Fariñas-Bermejo, Andrea; Grace, Ian; McVeigh, Doreen; Powers, Megan M.; Van Audenhaege, Loïc; Maslakova, Svetlana; Young, Craig M.; Van Dover, Cindy L. (Frontiers in Marine Science, 2020)
Methane seeps provide a variety of ecosystem services, including the provision of complex habitat structures and high levels of primary production, which can act as trophic support to non-seep-endemic species in an otherwise food-limited environment. The discovery of hundreds of seeps on the US Atlantic margin, ranging in depth from ~50 to 1700m, provides the opportunity to assess depth-related differences in seep-associated communities. Here, we use photo transects to characterize the megafaunal communities at six seeps along the US Atlantic margin, comparing taxonomic richness and community structure (taxon-abundance patterns) at shallow (~400m) and deep (~1500m) seeps. We use molecular analysis to identify the mussel species present and stable isotope analysis to explore the trophic ecology of bathymodiolin mussels and red crabs (Chaceon quinquedens). Our results suggest a faunal boundary exists between shallow and deep seeps; depth, and the co-varying factor temperature, explained 72% of the variation observed in taxon-abundance patterns. All mussel samples were identified as Bathymodiolus childressi, extending the known dominance of B. childressi at seeps near Baltimore Canyon to seeps off New England. Stable isotope analyses suggest B. childressi relies predominantly, if not entirely, on methane-derived nutrition at both shallow and deep seeps. For red crab, the proportion of methane-derived carbon within muscle tissue is highly variable, contributing ~0% of nutrition for crabs sampled at Shallop East and West but ~30% and ~50% of nutrition for two individuals sampled at Chincoteague East. In addition to red crabs using seeps as a food resource, invertebrate larvae samples and observational data suggests Chincoteague East may act as a reproductive hotspot for red crabs. Fifteen mating pairs, three ovigerous females, and numerous zoea larvae (identified as belonging to C. quinquedens) were observed at or above Chincoteague East, providing what we believe is the first evidence that some seeps may act as a reproductive hotspot for a commercially valuable species. This study highlights two ways that seeps may support fishery productivity (i.e. providing trophic support and increasing reproductive success) and encourages future research exploring the connection between deep-sea chemosynthetic ecosystems and commercially valuable species.